Is a claim for post-employment victimisation currently permissible under the Equality Act 2010?. (June 2014) - Middlemiss, Sam
This article provides an overview of the current legal rules dealing with post-employment victimisation and an analysis of the nature and scope of the law on this issue in the United Kingdom. The main focus of the article is to consider the conflicting legal decisions in this area and the impact they have had. Particularly, the detrimental effect the uncertainty arising from these cases has had, and will continue to have, on solicitors involved in claims and employees that have experienced this kind of victimisation. Finally, the need for reform of the law in this area will be considered.